Somewhere on the border - Akerman, Anthony (Wits University Press, 2012)
Somewhere on the Border was written by Anthony Akerman while in exile more than two decades ago. The play was intercepted in the post and banned as a publication by the apartheid censors because the language was considered 'offensive' and the portrayal of the South African Armed Forces 'prejudicial to the safety of the state'. This publication of a one act version of the play brings the South African Border War back into public discourse and pierces through the armour of silence, secrecy and shame that still surrounds it. The script is complemented by an author's preface and an afterword by historian Gary Baines, as well as photographs of its 2011 production.